DETERMINANTS OF BANK PROFITABILITY: EVIDENCE FROM THE CZECH BANKS - Černohorská, Liběna; Koťátkková Stránská, Pavla; Broklová, Karolína (Varazdin Development and Entrepreneurship Agency, 2019)
This paper is focused to construct model to examine the influence of selected determinants of profitability in the Czech banking sector. The goal of composing the simultaneous equation model is to verify and roughly quantify the assumed relationship between profitability in the Czech banking sector and selected determinants (variables) in period 2004–2017, i.e., 481 observations. As a part of the model that was designed, we verified the hypothesis that profitability in the Czech banking sector depends on selected determinants at a 0.05 level of significance. We tested the given data with the goal of verifying the proposed hypotheses on whether profitability (ROA, ROE) in the Czech banking sector is influenced by capital adequacy, balance sheet, taxation rate, the central bank's interest rates and GDP per capita. For verifying the hypotheses, we created a 2–equation model with nine variables.The model is estimation for two stochastically variable. The composed simultaneous equation confirmed influence was also confirmed only for certain determinant. The research question verifies the assumption that the ROE ratio is positively influenced by the inflation rate and the central bank’s interest rates. The second equation assesses the mutual ties between ROA ratio and capital adequacy, taxation rate and gross domestic product per capita. The research question verifies the assumption that the ROA ratio is negatively influenced by the taxation rate and GDP per capital. The ROA has the heterogeneous relationship with capital adequacy. All the Czech banks analysed were achieved statistically significant influence of taxation rate on ROA. Using the proposed simultaneous equation model, it is possible to verify and roughly quantify the assumed relationship between the Czech banking sector's profitability and selected determinants.
Determinanty ziskovosti bank: případové studie českých bank
Keywords: Czech bank; identifiability; profitability; simultaneous equations; české banky; ziskovost; simultánní rovnice